Degradation of the transcription factors PIF4 and PIF5 under UV‐B promotes UVR8‐mediated inhibition of hypocotyl growth in Arabidopsis. (7th November 2019) - Tavridou, Eleni; Pireyre, Marie; Ulm, Roman
Summary: Inhibition of hypocotyl growth is a well‐established UV‐B‐induced photomorphogenic response that is mediated by the UV‐B photoreceptor UV RESISTANCE LOCUS 8 (UVR8). However, the molecular mechanism by which UVR8 signaling triggers inhibition of hypocotyl growth is poorly understood. The bZIP protein ELONGATED HYPOCOTYL 5 (HY5) functions as the main positive regulatory transcription factor in the UVR8 signaling pathway, with HY5‐HOMOLOG (HYH) playing a minor role. However, here we demonstrate that hy5 hyh double mutants maintain significant UVR8‐dependent hypocotyl growth inhibition. We identify UVR8‐dependent inhibition of the activities of bHLH transcription factors PHYTOCHROME INTERACTING FACTOR 4 (PIF4) and PIF5 as part of the UVR8 signaling pathway, which results in inhibition of hypocotyl growth. The UVR8‐mediated repression of several hypocotyl elongation‐related genes is independent of HY5 and HYH but largely associated with UVR8‐dependent degradation of PIF4 and PIF5, a process that consequently diminishes PIF4/5 target promoter occupancy. Taken together, our data indicate that UVR8‐mediated inhibition of hypocotyl growth involves degradation of PIF4 and PIF5. These findings contribute to our mechanistic understanding of UVR8‐induced photomorphogenesis and further support the function of PIFs as integrators of different photoreceptor signaling pathways. Significance Statement: This work describes a role for degradation of PIF4 and PIF5 in the core UVR8 signaling pathway associated with UV‐B‐induced gene repression and inhibition of hypocotyl growth.